Mujeres, aprendizaje dialógico y transformación social - Carmen Elboj Saso; Ainoa Flecha Fernández (Universidad de La Rioja, 2013)
In the context of information societies, non academic women find themselves in a situation of double exclusion: firstly due to their condition as women and secondly due to their lack of academic knowledge in a context in which the level of formal education is more and more important. This article deals with and studies in depth the transformation possibilities that enclose the voice of those women who have traditionally been excluded from education, and therefore from long life learning and social participation. The theme of women has been treated from the academic world within the analysis of social inequalities and education. On the one hand, one of the issues which have been poorly studied is the role of non formal education in the life of non academic women. Education is usually based on academic conceptions of education, whilst currently in information society it is being proved that education depends more and more on the correlation between what we learn in the classrooms and what is learned out of the academic contexts. On the other hand, although the issue on women is being dealt with, the situation of non academic women in not being taken into consideration. In this sense, we believe that with the treatment of this subject not only do we agree with the lines of research from international scientific community, but also do we contribute to the formulation of new proposals of social participation and education through dialogic learning and dialogic feminism in which dialogic adult education is based.